Brief report on the archaeological findings at Baturyn in 2016 - Mezentse, V.I.; Sytyi, Yu.M.; Kovalenko, Yu.O. (Сіверщина в історії України, 2017)
This article presents the results of the latest archaeological and
architectural research on ceramic floor patterns and exterior decoration
of Hetman Ivan Mazepa’s palace in Baturyn and their Polish and Italian
analogies. It also describes recently excavated fi nds, which broaden our
knowledge about the wealth, culture, and lifestyle of the Cossack elite,
architectural majolica, and metalworks in early modern Baturyn, as well
as its commercial and artistic ties to Europe. Стаття підсумовує результати останніх архітектурно-археологічних досліджень типів мощення керамічних підлог і декору екстер’єру палацу гетьмана Івана Мазепи у Батурині, їх польських
та італійських аналогій. Також розглядаються знахідки з розкопок
2016 р., які доповнюють наші знання про багатство, культуру й побут козацької еліти, архітектурну майоліку і металеві вироби ранньомодерного Батурина, його торгові та мистецькі зв’язки з Європою. В статье изложены результаты последних архитектурно-археологических исследований типов мощения керамических полов и декора экстерьера дворца гетмана Ивана Мазепы в Батурине,
их польских и итальянских аналогий. Также рассматриваются
находки из раскопок 2016 г., которые дополняют наши знания о
благосостоянии и быте казацкой элиты, архитектурной майолике и металлических изделиях раннемодерного Батурина, его торговых и культурных связях с Европой.